Synthesis of non-fouling poly[N-(2-hydroxypropyl)methacrylamide] brushes by photoinduced SET-LRP1. Issue 23 (21st June 2015) - Vorobii, Mariia; de los Santos Pereira, Andres; Pop-Georgievski, Ognen; Kostina, Nina Yu.; Rodriguez-Emmenegger, Cesar; Percec, Virgil
<x xml:space="preserve">Abstract</x> Surface-initiated photoinduced SET-LRP of N-(2-hydroxypropyl)methacrylamide from an initiator-containing monolayer yields micropatterned brushes resistant to blood plasma fouling.